The Effect of Learners Mother Tongue on their Writings in English: An Error Analysis Study - Zulianti, Hajjah (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
The researcher takes the data from fifth semester studentsâ composition. Based on the analysis, the researcher found three types of learnersâ errors, namely grammatical errors, lexical errors, and word order errors. Grammatical errors include simple predicate missing: be, failure to attach âs, article missing, do auxiliary: underuse in negative sentence, singular and plural markers, misusing pronouns, possessive case incorrect: omission of âs, inappropriate preposition . Lexical errors include formal errors and semantic errors, and word order errors include misordering noun and adjective. The highest frequency of errors lies on the use of pronouns in writings. The errors may come from two possible causes; they are limited L2 environment and limited L2 performance.